Risk assessment with intellectually disabled offenders - Furniss, Lauren (2018)
This thesis presents a detailed perspective of the use and predictive ability of the Historical Clinical Risk Management-20 (HCR-20) violence risk assessment tool with intellectually disabled (ID) offenders. The aim is to explore the use of the HCR-20 within this population and aid clinicians in considering risk related needs of these offenders. A systematic review is presented focused on the predictive abilities of the HCR-20 across different mental health diagnoses. The review identified seven publications that compared the predictive ability of the HCR-20 across diagnostic categories. The review further identified four publications focused on predictive ability of the HCR-20 specifically with ID offenders, five focused on personality disordered offenders and three focused on offenders with a diagnosis of schizophrenia. Findings indicated that whilst the HCR-20 had good predictive abilities in general, there were differences in effect sizes across diagnostic groups and HCR-20 scales. This was followed by an empirical study that investigated the predictive ability of the HCR-20 for violent incidents across ID and mental health pathways within a high secure and low secure forensic setting. Results highlighted which of the HCR-20 scales, for both Version 2 and Version 3 of the tool, were positively correlated to frequency of violent incidents. This was followed by a case study of an older adult male offender with a diagnosis of ID, where the HCR-20 was used to inform psychological treatment and risk management. Limitations of the HCR-20 within clinical practice are also discussed. Finally, a critical appraisal of the HCR-20, with focus on application with ID offenders, is presented. Results indicated good levels of inter-rater reliability and predictive validity of the tool. The differences in the reported predictive ability of the HCR-20 across the research studies presented throughout the thesis are discussed, and further research recommended in line with these findings.